Effect of atomic vacancy on the electronic and optical properties, quantum capacitance of Zr2CO2-based electrodes. (August 2021) - Li, Xiao-Hong; Jia, Hao-Yuan; Li, Shan-Shan; Cui, Hong-Ling
Abstract: Density functional theory calculation is used to investigate the effect of atomic vacancy on stability, electronic and optical properties, quantum capacitance and surface charge storage of pristine and vacancy-defected Zr2 CO2 MXenes. The introduction of O vacancy results in the decrease of band gap, while the introduction of C and Zr vacancies results in the semiconductor-metal transition. The introduction of Zr vacancy results in the appearance of magnetism, which is contributed by O-py, O-px, C-pz, Zr-dz2, Zr-dyz states. The analysis of optical properties indicates that the introduction of the vacancy can make the absorption spectra of the systems more sensitive to the infrared light, and reflectivity is improved, especially in the infrared region. For asymmetric supercapacitor, pristine Zr2 CO2 MXene with Zr vacancy can be considered as the potential cathode material, while pristine Zr2 CO2 MXenes with C and O vacancy are potential anode materials through the analysis of quantum capacitance and surface charge storage. The increase mechanism of quantum capacitance is further explored through the analysis of density of states. Highlights: The introduction of C and Zr vacancy results in the semiconductor-metal transition. The introduction of Zr vacancy results in the appearance of magnetism, which is contributed by O-py, O-px, C-pz, Zr-dz2, Zr-dyz states. The absorption spectra of studied systems are more sensitive to the infrared light because of the introduction of vacancy. PZ-VZr is a promising cathode material, while PZ-VC and PZ-VO MXenes are potential anode materials.